Test Static Tradeoff Models Against Pecking Order Models of Capital Structure in UK Firms - Wu, Jinhua (2013)
This paper aims at testing the static tradeoff theory and the pecking order theory against British companies during the period of 2008 to 2012. A total sample of 40 companies listed on London Stock Exchange have been established. Through panel data analysis, this study investigates which of these two theories could better explain the capital structures of companies in the United Kingdom. The empirical analysis demonstrates that the static tradeoff theory has a better explanatory power for British firms while the pecking order theory does not really work in the UK during the selected study time period. Keywords: capital structure, the static tradeoff theory, the pecking order theory